Level of detail for 3D graphics - Luebke, David P. (Morgan Kaufmann series in computer graphics and geometric modeling., 2003)
Level of detail (LOD) techniques are increasingly used by professional real-time developers to strike the balance between breathtaking virtual worlds and smooth, flowing animation. Level of Detail for 3D Graphics brings together, for the first time, the mechanisms, principles, practices, and theory needed by every graphics developer seeking to apply LOD methods. Continuing advances in level of detail management have brought this powerful technology to the forefront of 3D graphics optimization research. This book, written by the very researchers and developers who have built LOD technology, is both a state-of-the-art chronicle of LOD advances and a practical sourcebook, which will enable graphics developers from all disciplines to apply these formidable techniques to their own work. * Is a complete, practical resource for programmers wishing to incorporate LOD technology into their own systems. * Is an important reference for professionals in game development, computer animation, information visualization, real-time graphics and simulation, data capture and preview, CAD display, and virtual worlds. * Is accessible to anyone familiar with the essentials of computer science and interactive computer graphics. * Covers the full range of LOD methods from mesh simplification to error metrics, as well as advanced issues of human perception, temporal detail, and visual fidelity measurement. * Includes an accompanying Web site rich in supplementary material including source code, tools, 3D models, public domain software, documentation, LOD updates, and more. Visit http://LODBook.com.